Relationship Between High Sensitivity C-reactive Protein and CagA Positive Helicobacter pylori in Cardiac Syndrome X - Rasmi, Y.; Seyed-Mohammadzad, M. H.; Raeisi, S. (Journal of Scientific Research, 2013)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Cytotoxin-associated gene A (CagA) may induce a persistent systemic inflammatory response in cardiac syndrome X (CSX). We aimed to evaluate relationship of CagA status and high sensitivity C-reactive protein (hs-CRP) in CSX patients. Sixty CSX patients and 60 gender matched controls were enrolled. Plasma samples were tested in terms of the presence of IgG antibody to Helicobacterpylori (anti-H. pylori) and CagA (anti-CagA) using ELISA method. Also, plasma level of hs-CRP was measured by ELISA method. CSX patients were detected to have significantly higher plasma hs-CRP level in comparison with the control ones (3.64 ± 3.07 vs. 0.54 ± 0.49, µg/ml, P = 0.0001). Plasma levels of hs-CRP in CSX patients with anti-CagA+ were significantly higher than those in anti-CagA(-) (CSX: 4.66±3.63 vs. 2.58±1.95 µg/ml, P = 0.011). Also, plasma levels of hs-CRP in the controls with anti-CagA+ were significantly higher than those in anti-CagA- (1.05±0.68 vs. 0.32±0.31 µg/ml, respectively, P = 0.004). The present data suggested that CagA status was probably associated with susceptibility to severe CSX by causing inflammation. The evidence for this hypothesis indicated that levels of hs-CRP increased in anti-CagA+ patients compared to the anti-CagA- ones. Keywords: Cardiac syndrome X; Helicobacter pylori; Inflammation ; hs-CRP, Cytotoxin-associated gene A. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i3.14171 J. Sci. Res. 5 (3), 527-533 (2013) <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->